Analysis of factors influencing interest in the use of mobile Banking - Sri Liniarti; Rizky Surya Andhayani Nasution (Institute of Computer Science (IOCS), 2023)
This study aims to examine what factors determine bank customers in the use of mobile banking services. This research method is quantitative discriptive, which is an approach that describes problems based on data in the form of numbers, then further analyzed for conclusions. This study took a sample of bank customers who have used mobile banking. Samples were taken using axial sampling techniques, from the number of respondents 101.Testing was carried out using the Spss program. Of the four variables in this study, three of them are proven, namely the perception of ease of use, risk perception affecting customers and access ability has a significant effect on interest in using mobile banking services. While the variable of perceived benefits does not have a significant effect on interest in using mobile banking services.